Α-Tocopherol/lipid ratio in blood is decreased in patients with Leber's hereditary optic neuropathy and asymptomatic carriers of the 11778 mtDNA mutation. Issue 3 (1st March 2001) - Klivenyi, P; Karg, E; Rozsa, C; Horvath, R; Komoly, S; Nemeth, I; Turi, S; Vecsei, L
Abstract : OBJECTIVES: Leber's hereditary optic neuropathy (LHON) is a maternally inherited disease characterised by acute or subacute bilateral visual loss in young patients. The primary aetiological event is a mutation in the mitochondrial genome (mtDNA) affecting in most cases mtDNA-encoded subunits of the respiratory chain NADH: coenzyme Q oxidoreductase (complex I). The impaired function of complex I leads to a decline in mitochondrial energy production and enhances free radical generation. METHODS: The concentrations of some non-enzymatic antioxidants (α-tocopherol, β-carotene, lycopene, glutathione, free sulphydryl groups) and the lipid peroxides in the blood of patients with LHON, carriers with homoplasmic DNA mutation at 11 778, and controls were investigated using high performance liquid chromatography and spectrophotometric methods to assess the function of their antioxidant defence systems. RESULTS: The α-tocopherol/cholesterol+ triglyceride ratio was significantly reduced (p<0.05) both in the patients and asymptomatic carriers. The concentrations of the other antioxidants and the lipid peroxides were not different from those of control subjects. CONCLUSION: The low concentration of plasma α-tocopherol most probably reflects the consumption of the antioxidant by the affected tissues. Furthermore, it suggests that α-tocopherol may be the primary scavenger molecule against the free radicals induced by complex I deficiency.